Cognitive Function Is Impaired in Patients with Recently Diagnosed Type 2 Diabetes, but Not Type 1 Diabetes. (9th August 2018) - van Gemert, Theresa; Wölwer, Wolfgang; Weber, Katharina S.; Hoyer, Annika; Strassburger, Klaus; Bohnau, Nora T.; Brüggen, Marie A.; Ovelgönne, Katharina; Gössmann, Eva-Maria; Burkart, Volker; Szendroedi, Julia; Roden, Michael; et al.
Abstract : Objective . To test whether cognitive function is impaired in early states of diabetes and to identify possible risk factors for cognitive impairment. Methods . A cross-sectional analysis within the German Diabetes Study included patients with type 1 or type 2 diabetes within the first year after diagnosis or five years after study inclusion and metabolically healthy individuals. Participants underwent comprehensive metabolic phenotyping and testing of different domains of cognitive function. Linear regression models were used to compare cognition test outcomes and to test associations between cognitive function and possible influencing factors within the groups. Results . In participants with recently diagnosed diabetes, verbal memory was poorer in patients with type 2 diabetes (P = 0.029 ), but not in type 1 diabetes (P = 0.156 ), when compared to healthy individuals. Five years after diagnosis, type 2 diabetes patients also showed lower verbal memory than those with type 1 diabetes (P = 0.012 ). In addition to crystallized intelligence, a higher body mass index among individuals with recently diagnosed type 2 diabetes and male sex among individuals with recently diagnosed type 1 diabetes were associated with impaired verbal memory (allP < 0.05 ). Conclusion . Verbal memory is impaired in individuals with recently diagnosed type 2 diabetes and likely associated with higher body mass. This trial is registered with the trial registration numberNCT01055093 .